2015
DOI: 10.1021/acsnano.5b01803
|View full text |Cite
|
Sign up to set email alerts
|

Lattice-Directed Formation of Covalent and Organometallic Molecular Wires by Terminal Alkynes on Ag Surfaces

Abstract: Surface reactions of 2,5-diethynyl-1,4-bis(phenylethynyl)benzene on Ag(111), Ag(110), and Ag(100) were systematically explored and scrutinized by scanning tunneling microscopy, molecular mechanics simulations, and density functional theory calculations. On Ag(111), Glaser coupling reaction became dominant, yielding one-dimensional molecular wires formed by covalent bonds. On Ag(110) and Ag(100), however, the terminal alkynes reacted with surface metal atoms, leading to one-dimensional organometallic nanostruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
134
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(144 citation statements)
references
References 62 publications
10
134
0
Order By: Relevance
“…The STM data ( Figure a) evidence polymeric wires of irregular shape resulting from a mixture of the targeted linear coupling (green circles) with twofold connections with varying bending angles (black) and a variety of threefold covalent linking motifs (red). Additionally, some connections with a sphere‐shaped protrusion between monomers (blue) are consistent with the expected geometry and appearance of Ag bis‐acetylides . Specifically, the large number of branched covalent connections obstructs the fabrication of linear, 1D nanowires with a precise structure.…”
mentioning
confidence: 54%
“…The STM data ( Figure a) evidence polymeric wires of irregular shape resulting from a mixture of the targeted linear coupling (green circles) with twofold connections with varying bending angles (black) and a variety of threefold covalent linking motifs (red). Additionally, some connections with a sphere‐shaped protrusion between monomers (blue) are consistent with the expected geometry and appearance of Ag bis‐acetylides . Specifically, the large number of branched covalent connections obstructs the fabrication of linear, 1D nanowires with a precise structure.…”
mentioning
confidence: 54%
“…Sterically shielding the terminal alkyne functionalities was also applied by Wang, Zhao, Wu, and co‐workers to prepare linear, fully π‐conjugated polymeric chains . It is noteworthy that the authors observed along with the Glaser products, organometallic bisalkynylmetal species.…”
Section: On‐surface C−h Activation Reactions For C−c Bond Formationmentioning
confidence: 99%
“…[5][6][7][8][9] Thus on-surface synthesis demonstrates remarkable potential in the fabrication of novel nanostructures/nanomaterials that still remain challenging to be obtained by traditional synthetic methods.F or instance, carbon materials,i ncluding fullerenes,g raphene,g raphene nanoribbons,s ingle-chirality carbon nanotubes,a nd metalated carbyne,a sw ell as different hydrocarbons have been successfully fabricated by such on-surface synthetic strategies. [15][16][17][18][19] Thed emand for acetylenic scaffolds is due to the emergence of carbon nanostructures/nanomaterials,s uch as one-dimensional linear carbon (i.e., carbyne) and two-dimensional graphyne/ graphdiyne structures,w hich contain sp-hybridized carbon atoms.H owever,s cientific and technological advances made with these interesting carbon nanomaterials are significantly impeded by the high chemical activity of sp-hybridized carbon atoms.O n-surface CÀXb ond activation followed by aC ÀC coupling provides ar elatively efficient route to the synthesis of acetylenic linkages. [15][16][17][18][19] Thed emand for acetylenic scaffolds is due to the emergence of carbon nanostructures/nanomaterials,s uch as one-dimensional linear carbon (i.e., carbyne) and two-dimensional graphyne/ graphdiyne structures,w hich contain sp-hybridized carbon atoms.H owever,s cientific and technological advances made with these interesting carbon nanomaterials are significantly impeded by the high chemical activity of sp-hybridized carbon atoms.O n-surface CÀXb ond activation followed by aC ÀC coupling provides ar elatively efficient route to the synthesis of acetylenic linkages.…”
mentioning
confidence: 99%
“…[15][16][17][18][19] However,t he further functionalization of these molecular precursors with additional alkynyl groups to form carbon allotropes (e.g., graphdiyne) is hampered by the increasing instability of the precursors (e.g.,hexaethynylbenzene). [15][16][17][18][19] However,t he further functionalization of these molecular precursors with additional alkynyl groups to form carbon allotropes (e.g., graphdiyne) is hampered by the increasing instability of the precursors (e.g.,hexaethynylbenzene).…”
mentioning
confidence: 99%